2017
DOI: 10.15282/mohe.v6i1.80
|View full text |Cite
|
Sign up to set email alerts
|

Visual anticipation time differences between athletes in open and closed skills sports

Abstract: The ability to anticipation accurately and consistently plays a vital role to excel in sports performance. The present study was designed to determine the differences of visual anticipation time between dynamic and static sports. A total of 95 junior athletes, aged 13 to 16 years old (=14.84±1.04 years) from Bukit Jalil Sports School participated in the study. Participants were distributed to dynamic (n=47) and static (n=48) sports according to their sports participation. Visual anticipation time was tested u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 18 publications
0
1
1
Order By: Relevance
“…practice, all of the studied athletes practiced sport for more than three years at the moment of study. Besides, another study has not found any significant differences between time anticipation abilities of the sub-elite athletes practicing open and closed skills sports (Omar, Kuan, Knight, Manan, & Padri, 2017). Each group of the elite and the sub-elite athletes in our study practiced both open and closed skills sports that could also explain the lack of significant differences in time and movement anticipation between them.…”
Section: Discussioncontrasting
confidence: 47%
“…practice, all of the studied athletes practiced sport for more than three years at the moment of study. Besides, another study has not found any significant differences between time anticipation abilities of the sub-elite athletes practicing open and closed skills sports (Omar, Kuan, Knight, Manan, & Padri, 2017). Each group of the elite and the sub-elite athletes in our study practiced both open and closed skills sports that could also explain the lack of significant differences in time and movement anticipation between them.…”
Section: Discussioncontrasting
confidence: 47%
“…These results could be a reason for the increased rate of ACL injury in ball fields such as basketball and handball [8]. In addition, several studies have compared athletes in different fields in terms of predictability; these studies have shown that regular exercise improves the ability to predict, and athletes in the different fields differ significantly in the amount of predictability [10][11][12][13]. Also, Omar et al investigated the visual anticipation time differences between athletes in open and closed skills sports.…”
Section: Plain Language Summarymentioning
confidence: 99%